2021
DOI: 10.1016/j.cmi.2021.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and duration of protection after yellow fever vaccine in people living with human immunodeficiency virus: a systematic review

Abstract: Background: We lack the rationale on which to base the development of a yellow fever (YF) vaccination schedule for people living with human immunodeficiency virus (PLWHIV). Objectives: To report on the current evidence regarding the seroconversion rate and the duration of humoral protection after YF vaccine, as well as the impact of revaccination in PLWHIV. Data sources: MEDLINE, Google Scholar, LILACS and Cochrane CENTRAL were searched. Methods: We selected studies on PLWHIV of all ages (including perinatally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 52 publications
4
17
1
Order By: Relevance
“…Patients with hematologic cancers [ 58 ] had intermediate seroconversion rates (about 52%). Systematic reviews involving children [ 35 , 39 , 40 , 42 , 44 , 52 , 53 , 54 , 59 , 60 , 61 , 62 , 63 ] demonstrated findings consistent with those involving adults. An intervention that improved vaccine efficacy was the use of high-dose vaccines [ 35 , 37 , 42 , 44 , 45 , 51 ].…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Patients with hematologic cancers [ 58 ] had intermediate seroconversion rates (about 52%). Systematic reviews involving children [ 35 , 39 , 40 , 42 , 44 , 52 , 53 , 54 , 59 , 60 , 61 , 62 , 63 ] demonstrated findings consistent with those involving adults. An intervention that improved vaccine efficacy was the use of high-dose vaccines [ 35 , 37 , 42 , 44 , 45 , 51 ].…”
Section: Resultsmentioning
confidence: 75%
“…A total of 32 systematic reviews focused on non-COVID-19 vaccines ( Table 3 ). Several vaccines were studied, including inactivated hepatitis A vaccine [ 32 ], recombinant hepatitis B vaccine [ 33 , 34 , 35 , 36 , 37 , 38 ], recombinant human papillomavirus vaccines [ 39 , 40 ], inactivated influenza vaccine [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], live-attenuated measles vaccine (given post hematopoietic stem-cell transplantation [ 52 ] and in children living with human immunodeficiency virus [ 53 ]), pneumococcal conjugate and polysaccharide vaccines [ 46 , 49 , 54 , 55 , 56 ], live-attenuated and recombinant subunit zoster vaccines [ 57 , 58 ], live-attenuated yellow fever vaccine [ 59 ], and others [ 60 , 61 , 62 , 63 ]. Immunocompromised states studied included use of B-cell-depleting anti-CD20 therapy, chronic kidney failure, human immunodeficiency virus infection, immune-mediated inflammatory diseases, liver cirrhosis, malignancy, post-splenectomy status, and solid organ transplant recipients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis of studies on 17D vaccination of people living with HIV, it was found that 97.6% of the population seroconverted. Between one and 10 years after vaccination, a mean of 72% of this population still had neutralizing antibodies, and after 10 years, a mean of 62% still had neutralizing antibodies [ 50 ]. However, HIV-infected individuals who had suppressed plasma HIV RNA at the time of 17D vaccination had up to 100% seropositivity at 10 years post-vaccination, which is comparable to non-HIV-infected individuals [ 49 ].…”
Section: Live-attenuated 17d Vaccinementioning
confidence: 99%
“…Since 2013, the WHO has recommended a single dose of YFV for life-long immunity [1], but the French authorities still recommend a booster vaccination 10 years after the first dose before a new departure to an endemic area for persons living with HIV if there is no contraindication [2]. In a recent metaanalysis, 1-10 years after yellow fever vaccination, persistence of neutralizing antibodies was reported in less than 75% of HIV-infected adults [3].We prospectively studied live attenuated 17D primingvaccination in HIV-infected (HIV-positive) adults under antiretroviral therapy with CD4 þ cell counts above 350 cells/ml and HIV-uninfected (HIV-negative) adults in the ANRS EP46 NOVAA study [4]. The objective of this extended study was to evaluate the persistence of immunity for up to 5 years.…”
mentioning
confidence: 99%